Compilation of Smart Cities Attributes and Quantitative Identification of Mismatch in Rankings - Osama A. Marzouk (Journal of Engineering)
One practical way to define a “smart city” is to look at the specific qualities listed in a ranking study about smart cities. Such method gives de facto guidelines for classifying a city as being smart or not. Building upon this rationale, the current work in its first objective presents features adopted in evaluating the “smartness” of cities in seven evaluations and in its second objective arranges them in a suggested structure of six scopes with forty-three keywords. With these two objectives, the current study serves as a summary of various ranking studies in terms of being a collection place of many evaluation criteria. Four of the considered studies are the 2018 and 2019 annual editions from two sources, and comparing these criteria shows some changes over one year, and these updates are highlighted. A third objective of this study considers analyzing assigned ranks and utilizing a normalized score (limited to a maximum of unity) derived from the raw scores given in six ranking studies (out of the seven considered, with one ranking study excluded as it does not give raw numerical scores) to the six cities that commonly appear in all of them. This part shows with details the existence of mismatch not just in a one-time ranking, but also in a year-to-year trend, where a city appears to be improving according to one evaluator while appears to be degrading according to another evaluator. As a fourth objective, statistical analysis of the evaluation results was conducted, with quantitative assessment of rankings mismatch.